Elaborasi Perkembangan Teori Viktimologi Terhadap Anak Sebagai Korban Tindak Pidana Kekerasan Dalam Rumah Tangga - M. Ali Akbar; Sri Ramyanti; Ayu Efritadewi (Social Issues Quarterly, 2023)
This research is entitled Elaboration of the Development of Victimology Theory of Children as Victims of Domestic Violence Crimes, with identification of the problem of how the law protects the problem of how the law protects children as victims of criminal acts of domestic violence and what factors are the obstacles in providing legal protection to children and what efforts should be made. The purpose of this research is to find out how legal protection is for children as victims of domestic violence and to find out what are the obstacles encountered in providing legal protection for children as victims of domestic violence and what efforts can be made to overcome these obstacles. Which the results of the study show that the influencing factors can lead to criminal acts of domestic violence against children which we can see from economic, environmental factors and the lack of supervision from parents.